Transgenerational genomic analyses reveal allelic oscillation and purifying selection in a gut parasite Nosema ceranae - Wei, Xiuxiu; Zheng, Jialan; Evans, Jay D.; Huang, Qiang (Frontiers in Microbiology, 2022)
Standing genetic variation is the predominant source acted upon by selection. Organisms with high genetic diversity generally show faster responses toward environmental change. Nosema ceranae is a microsporidian parasite of honey bees, infecting midgut epithelial cells. High genetic diversity has been found in this parasite, but the mechanism for the parasite to maintain this diversity remains unclear. This study involved continuous inoculation of N. ceranae to honey bees. We found that the parasites slowly increased genetic diversity over three continuous inoculations. The number of lost SNVs (Single Nucleotide Variants) was balanced with novel SNVs, which were mainly embedded in coding regions. Classic allele frequency oscillation was found at the regional level along the genome, and the associated genes were enriched in apoptosis regulation and ATP binding. The ratio of synonymous and non-synonymous substitution suggests a purifying selection, and our results provide novel insights into the evolutionary dynamics in microsporidian parasites.